Socratic epistemology: Explorations of knowledge-seeking by questioning - Hintikka, Jaakko (Cambridge University, 2013)
Socratic Epistemology challenges most current work in epistemology-which deals with the evaluation and justification of information already acquired-by discussing instead the more important problem of how knowledge is acquired in the first place. Jaakko Hintikka's model of information-seeking is the old Socratic method of questioning, which has been generalized and brought up to date through the logical theory of questions and answers that he has developed. Hintikka argues that the quest by philosophers for a definition of knowledge is ill-conceived and that the entire notion of knowledge should be replaced by the concept of information. And he further offers an analysis of the different meanings of the concept of information and of their interrelations. The result is a new and illuminating approach to the field of epistemology.